“Listen to Him!”: Angelic and Divine Typology in Mark’s Transfiguration Account - Robinson, Jonathan Rivett (Horizons in biblical theology, 2024)
In this study I will argue that, while Matthew and Luke’s redaction of the Markan Transfiguration present Jesus as the antitype of Moses, Mark’s own account does not. Rather, Mark uses typology to narrate Jesus into the stories of Elijah and Moses, both of whom are described in the Jewish scriptures as ascending a mountain to talk with God in narratives in which the Angel of YHWH also features. Distinctive features of Mark’s account suggest that Mark wishes to associate Jesus, not with Moses, but with YHWH and his angel, using the scriptural ambiguity between the Angel of YHWH and Israel’s God to generate a similar ambiguity around the divine identity of Jesus. Consequently, Mark’s Transfiguration presents a “higher” Christology than that of the Transfigurations in the other Synoptic Gospels. In Mark’s Transfiguration, Jesus is compared, not to human prophets, but to the anthropomorphic manifestations of Israel’s God at Sinai and Horeb.